Unravelling the Importance of Diazotrophy in Corals – Combined Assessment of Nitrogen Assimilation, Diazotrophic Community and Natural Stable Isotope Signatures - Bednarz, Vanessa N.; van de Water, Jeroen A. J. M.; Grover, Renaud; Maguer, Jean-François; Fine, Maoz; Ferrier-Pagès, Christine (Frontiers in Microbiology, 2021)
There is an increasing interest in understanding the structure and function of the microbiota associated with marine and terrestrial organisms, because it can play a major role in host nutrition and resistance to environmental stress. Reef-building corals live in association with diazotrophs, which are microbes able to fix dinitrogen. Corals are known to assimilate diazotrophically-derived nitrogen (DDN), but it is still not clear whether this nitrogen source is derived from coral-associated diazotrophs and whether it substantially contributes to the coral’s nitrogen budget. In this study, we aimed to provide a better understanding of the importance of DDN for corals using a holistic approach by simultaneously assessing DDN assimilation rates (using 15N2 tracer technique), the diazotrophic bacterial community (using nifH gene amplicon sequencing) and the natural δ15N signature in Stylophora pistillata corals from the Northern Red Sea along a depth gradient in winter and summer. Overall, our results show a discrepancy between the three parameters. DDN was assimilated by the coral holobiont during winter only, with an increased assimilation with depth. Assimilation rates were however not linked to the presence of coral-associated diazotrophs, suggesting that the presence of nifH genes does not necessarily imply functionality. It also suggests that DDN assimilation was independent from coral-associated diazotrophs and may instead result from nitrogen derived from planktonic diazotrophs. In addition, the δ15N signature presented negative values in almost all coral samples in both seasons, suggesting nitrogen sources other than DDN in contributing to the nitrogen budget of corals from this region. This study yields novel insight into the origin and importance of diazotrophy for scleractinian corals from the Northern Red Sea using multiple proxies.